CONSUMERS’ PERCEPTION AND WILLINGNESS TO PAY FOR ORGANIC TOMATOES IN OFORIKROM MUNICIPAL, ASHANTI, GHANA - Fred Nimoh; Alexander Annor Frimpong; Ambrose Azenyinkajigi Adama; Enock Kwame Tham-Agyekum (Apstract: Applied Studies in Agribusiness and Commerce)
Although conventional tomatoes are often preferred by consumers, organic tomatoes are thought to be safer and healthier. This is because some customers do not fully comprehend the advantages of organic tomatoes. The purpose of this study was to investigate how customers perceive and are willing to pay for organic tomatoes. 399 systematically chosen respondents provided the data, which was collected. The data were analyzed using descriptive and inferential statistics such the Perception Index, Contingent Valuation Method, and Tobit Regression Model. The findings indicated that the majority of respondents were familiar with organic tomatoes. A perception rating of 1.24 indicates that respondents had a favorable opinion of organic tomatoes. Organic tomato buyers were willing to spend at least GHC 9.63 per kilo. Consumers' willingness to pay for organic tomatoes was influenced by their view of the health benefits, their level of education, their income, and their knowledge of and familiarity with organic tomatoes. As a result, the study advises producers or farmers to inform their customers about the health advantages of organic tomatoes and to focus on consumers with high incomes and educational levels since these factors greatly influenced their willingness to pay.